The evidence-based topical therapies for management of minor burns in outpatient clinic - Dien, Siphora; Miranda, Eliza; Pusponegoro, Erdina Hardiono D; Wardhana, Aditya (Journal of General - Procedural Dermatology and Venereology Indonesia, 2015)
Burns are often seen in clinics or hospitals. Majority of burns are minor burns, which can be managed in outpatient setting with satisfactory result. The healing outcome depends on physician’s knowledge and competencies in burn pathogenesis and basic principles of burn care. Initial treatment of burns consists of emergency evaluation, assessment of depth and severity of burns and considerations for referral. The principles of minor wound therapy include cooling, cleansing, pain management, and topical therapy. Recently, many topical agents are available and indicated for first to second degree burn. Silver sulfadiazine (SSD) is the standard treatment; however, it has some limitations. Scientific evidences showed that topical antibiotics do not reduce the incidence of local infection, invasive infection, and mortality of infection. Burns heal faster with hydrogel dressings and some other dressings compared to SSD. There are insufficient evidences to support the use of aloe vera, honey, and negative pressure wound therapy in burns. Moist exposed burn ointment (MEBO®) has been demonstrated to have equal efficacy to SSD.